The Theory of Balance in Physics and Islamic Governance: Exploring the Convergence of Natural Equilibrium and Social Balance within an Islamic State Context - Handayani, Yusri; Aderus, Andi; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This research examines the relationship between the concept of equilibrium in physics and the implementation of Islamic governance, and how the two concepts relate to each other in the context of an Islamic state. In physics, equilibrium is achieved through the interaction of various forces within a system that continuously strives for stability, both in static and dynamic systems. This parallels the efforts of Islamic governments to maintain a balance between state authority, individual rights, and social obligations. Islamic governments emphasize the importance of social justice, reflected in state policies based on Sharia law, which aim to ensure social welfare by equitably considering individual rights and societal interests. In this study, the authors found that Islamic governance must be able to adapt to changing times and social dynamics, similar to the principle of equilibrium in physics, which always strives to achieve a stable state despite change. Socio-economic policies such as zakat and waqf serve to reduce social inequality, while the moral and ethical principles of sharia play a crucial role in maintaining this balance. This study concludes that the concept of equilibrium in physics provides a useful perspective for understanding the dynamics of Islamic governance, which is not merely static but also dynamic and adaptive to the demands of the times and the needs of society.